From Lexicon to Flexicon: The Principles of Morphological Transcendence and Lexical Superstates in the Characterization of Words in the Mind - Libben, Gary (Frontiers in Artificial Intelligence, 2022)
The field of mental lexicon research has benefitted greatly from the founding metaphor of a dictionary in the mind. That metaphor, however, had its origins in a perspective in which the lexicon was seen as a static repository of representations with fixed structural properties. This paper presents a contrasting view. It is a view that highlights that words are activities that we perform, rather than simply representations that we have. It is proposed that lexical representations are best seen as hierarchies of action within a highly interconnected and dynamic system. The paper presents two principles of lexical organization: morphological transcendence and lexical superstates. The former principle claims that through the activities of language comprehension and production, lexical forms can develop variant forms. Thus, the form key may develop into forms such as key- (e.g., keyboard) and -key, (e.g., turnkey). The paper also discusses how transcendence leads to lexical superstates, which do not have a fixed morphological structure. As part of a lexical superstate, alternative morphological structures exist as potential realizations. Which one is actually realized will depend on the specific circumstances of a lexical action. An account is presented in which the effects of semantic transparency are treated in terms of transcendence and superstate interactions. It is claimed that this approach, which highlights the dynamic and flexible nature of the mental lexicon, has implications for how we approach the modeling of language and cognition in general.